Development of a Mini Soccer Game for 12-Year-Olds at Public Elementary School Sandana, Tolitoli Regency - Suhendra, Tesa Alex; sukrawan, nyoman; Adhan, Moh.; Rahmah, Rahmah Alex; Apriliansah, Egy (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. Examine This aims to design a little soccer game for educational participants in a school setting. Materials and Methods. The game was intended to be utilized by physical education teachers as a variety in learning, aimed at enhancing participants' enthusiasm in mini soccer education. Results. indicate that experts and teachers evaluate goods generated in accordance with the implementation of the School-Based Curriculum for 12-year-olds. Participants in the assessment are educated about the mini football game produced based on the results obtained from the completed questionnaire. According to participant education, 100% can complete the tasks, while 92% find the games easy to execute. Additionally, 92% of participants comprehend the regulations of the games taught, and 92% adhere to these regulations. Furthermore, 75% of participants report no difficulty in performing the games, and 92% express a preference for the tools utilized in play. Moreover, 92% find the games enjoyable and conducive to movement, 85% are capable of cooperation, and 75% of participants experience apprehension regarding the games taught. Conclusion. Study show that game Mini soccer is fun , safe , and effective For participant educate class on school basic . Validation experts and response participants demonstrate high eligibility, with considerable improvements in study results.